2006
DOI: 10.1016/j.jcrs.2006.02.037
|View full text |Cite
|
Sign up to set email alerts
|

Corneal thickness measurements in normal and keratoconic eyes: Pentacam comprehensive eye scanner versus noncontact specular microscopy and ultrasound pachymetry

Abstract: Results suggest that whereas Pentacam CES and UP may be used interchangeably in normal eyes in the clinical setting for the measurement of CCT, one should be cautious interpreting corneal thickness data from Pentacam CES, UP, and particularly SM in eyes with keratoconus. Whereas, in normal and mildly keratoconic eyes, Pentacam CES and UP demonstrated very high and comparable reproducibility, in moderately keratoconic eyes, Pentacam CES readings showed better reproducibility than UP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
91
3
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(110 citation statements)
references
References 23 publications
11
91
3
5
Order By: Relevance
“…Logistic regression was used to support the cutoff point identified with the ROC curve analysis. (5)(6)(7)(8)(9)(10)(11)(12)(13)(14) . However, accurate differentiation of keratoconus from healthy corneas is not yet sufficient, as there is a need to detect corneas with a higher susceptibility to becoming ectatic after laser photoablative surgery (15)(16) .…”
Section: Ability Of Corneal Biomechanical Metrics and Anterior Segmenmentioning
confidence: 99%
“…Logistic regression was used to support the cutoff point identified with the ROC curve analysis. (5)(6)(7)(8)(9)(10)(11)(12)(13)(14) . However, accurate differentiation of keratoconus from healthy corneas is not yet sufficient, as there is a need to detect corneas with a higher susceptibility to becoming ectatic after laser photoablative surgery (15)(16) .…”
Section: Ability Of Corneal Biomechanical Metrics and Anterior Segmenmentioning
confidence: 99%
“…However, proper patient selection is challenging in such cases, as preoperative thin corneas and thinner residual stromal bed after excimer laser ablation are widely described as risk factors for the development of postoperative ectasia (3)(4) . Healthy patients can present with thin corneas (≤505 μm), and keratoconic eyes can have a "normal" (≤520 μm) central corneal thickness (CCT) (5)(6)(7)(8) . For decision making in these cases, the surgeon should rely on analysis of corneal topography and tomography data (such as corneal volume, elevation maps and pachymetric distribution) (9)(10) .…”
Section: Introductionmentioning
confidence: 99%
“…Corneal thickness has been proposed to be a useful parameter for the clinical identification of keratoconus. 36,37 Studies using ultrasound 38,39 or slit-scanning technologies40 have found that the difference (or ratio) between the peripheral and the thinnest (or central) corneal thickness was significantly greater in eyes with keratoconus than in normal eyes. Corneal thickness measurements have some disadvantages.…”
Section: Discussionmentioning
confidence: 99%